2022
DOI: 10.1007/s11356-022-19246-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sewage sludge contribution during co-composting using cause-evidence-impact analysis based on morphological characterization

Abstract: The methods of compost preparation from sewage sludge and their modes of application to the agricultural elds have profound impacts on the soil ecology and environment. Besides their chemical conditioning effect on soil organic matter, they also impart physical attributes to the soil texture and structure. Though it is expected that compost addition improves water holding capacity and nutrient sequestration, there is lack of clarity in correlating the outcomes with conditions of excess nutrient storage/leachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…It is widely accepted that the recycling of agro-waste can be a critical aspect of sustainable agriculture and environmental conservation as it involves the conversion of agricultural residues and by-products into valuable resources, minimizing their negative impact on the environment. In order to provide some meaningful insights into the conflicting phenomena, we present a systematic analysis of critical operational factors, their evidences from the performance and the corresponding environmental impacts based on the concept of cause-evidence-impact methodology [13]. The first step of the analysis involves identification of key operational factors in the target utilization (concrete construction) (such as collection, preparation, use, disposal), followed by subsequent symptoms in the material properties (such as reduction in strength, visual defects, unexpected failure patterns), and mapping of the corresponding impacts (Figure 10).…”
Section: Environmental Considerations Of Agro-waste Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that the recycling of agro-waste can be a critical aspect of sustainable agriculture and environmental conservation as it involves the conversion of agricultural residues and by-products into valuable resources, minimizing their negative impact on the environment. In order to provide some meaningful insights into the conflicting phenomena, we present a systematic analysis of critical operational factors, their evidences from the performance and the corresponding environmental impacts based on the concept of cause-evidence-impact methodology [13]. The first step of the analysis involves identification of key operational factors in the target utilization (concrete construction) (such as collection, preparation, use, disposal), followed by subsequent symptoms in the material properties (such as reduction in strength, visual defects, unexpected failure patterns), and mapping of the corresponding impacts (Figure 10).…”
Section: Environmental Considerations Of Agro-waste Recyclingmentioning
confidence: 99%
“…Among all plant-based natural fibres, coconut fibres persist as the strongest with a mechanical strength of 21.51 MPa [12]. The length to diameter ratio (aspect ratio) of the fibres is found to have an impact on their elastic properties and the ability to rupture, typically pertaining to a parent material influence [13]. In case of pre-treated fibres, the final qualities result from the surface modifications and possible changes in the chemical composition [14].…”
Section: Introductionmentioning
confidence: 99%
“…India, with its growing population and evolving consumption patterns, produces a significant volume of organic wastes from households, agricultural activities, green spaces, local markets, and the food industry. While mismanaged organic wastes can pose severe environmental challenges including greenhouse gas emissions and groundwater contamination, they also offer substantial opportunities for resource recovery and circular economy principles [1][2][3][4][5]. On the other hand, industrial waste management and utilization play a vital role in achieving sustainable development goals, particularly IOP Publishing doi:10.1088/1755-1315/1258/1/012011 2 in rapidly growing economies like India.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, each of them vary in their micro-structural features, elemental compositions and therefore, inevitably, in their chemical reactivity with water. This has created many conflicts in the selection of building materials for construction especially when some of them exhibit opposing effects on the intended qualities of mortar and concrete [21][22][23][24][25][26][27][28][29][30]. In this scenario, combining two or more types of mineral admixtures has shown to be a better option than using only one admixture for improving the properties of mortar and concrete [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is distinctly evident that there exists no known standardized methodology for preparing such composite blends from the RPM which are available in various size, shape and compositions. On a preliminary investigation of the literature, it is revealed that most of the data-driven analytical research works rely on the morphological characterization techniques to evaluate the micro-structural evidence of physico-chemical compatibility of the composites [21][22][23][24]. Therefore, it is quite obvious to seek out the distinctive characteristics of various RPM composites using the inferences reported from the morphological studies [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%